On the location of host Ca atoms responsible for ferrimagnetism in the layered cobaltites YBaCo2O5.5 - Aurelio, Gabriela (2013)
Recent studies have shown that the addition of Ca as host ion in the layered compounds RBaCo2O5+δ (with R a rare earth or yttrium) produces a dramatic effect on their magnetic properties, as well as on their Seebeck coefficient and resistivity. Studies performed so far have opened up the possibility that the substitution site for Ca atoms might not be obvious, having been reported at the Y site, at the Ba site, or regarded as not decisive to the ferromagnetism enhancement. In this work, we present a comparative study of Ca-doped cobaltite samples synthesized with two different nominal substitution sites, namely, Ca replacing Ba, and Ca replacing Y. X-ray absorption spectroscopy performed at the Ca, Ba, and Co edges to study the local environment around these elements allowed to unequivocally determine that the substitutional site of Ca is the Y site. This important result helps to clarify the mixed valence state of cobalt as Co3+ and Co4+, which would be responsible for the ferromagnetic interactions, and explains the antiferromagnetic to ferrimagnetic switch occurring already at 10% Ca doping level.